Effects of a novel pesticide resistance management strategy on tick control in a smallholding exotic-breed dairy herd in Kenya - Kamidi, R.E.; Kamidi, M.K. (Springer, 2005)
Effects of a novel pesticide resistance management strategy on tick control are evaluated in this study. The study is based on a temporal analysis of tick management practices on a smallholding in western Kenya. Results are reported of an innovation to tackle individual resistance in a pair of alternative pesticides using relay application. Incidence of tick-borne diseases at the farm was reduced from 79.6% per annum to 4.5% and no cases were observed in the last two years of the study. Negative cross-resistance is believed to be the mechanism in play for this effective tick control practice. Tick-borne disease control and management costs were halved in comparison to application of a single ineffective pesticide at the same treatment frequency. The acaricide relay strategy is suitable for smallholdings and is expected to significantly extend the useful lifespan of the pesticide pair.